Host galaxy identification for binary black hole mergers with long baseline gravitational wave detectors. Issue 4 (29th November 2017) - Howell, E J; Chan, M L; Chu, Q; Jones, D H; Heng, I S; Lee, H-M; Blair, D; Degallaix, J; Regimbau, T; Miao, H; Zhao, C; Hendry, M; et al.
Abstract: The detection of black hole binary coalescence events by Advanced LIGO allows the science benefits of future detectors to be evaluated. In this paper, we report the science benefits of one or two 8 km arm length detectors based on the doubling of key parameters in an Advanced LIGO-type detector, combined with realizable enhancements. It is shown that the total detection rate for sources similar to those already detected would increase to ∼ 10 3 –10 5 per year. Within 0.4 Gpc, we find that around 10 of these events would be localizable to within ∼10 −1 deg 2 . This is sufficient to make unique associations or to rule out a direct association with the brightest galaxies in optical surveys (at r -band magnitudes of 17 or above) or for deeper limits (down to r -band magnitudes of 20) yield statistically significant associations. The combination of angular resolution and event rate would benefit precision testing of formation models, cosmic evolution, and cosmological studies.